Episodicity of seismicity accompanying melt intrusion into the crust - White, R. S.; Redfern, S. A. T.; Chien, S-Y (Geophysical Research Letters, 2012)
Microseismicity from a dike intruding the mid-crust of Iceland occurs episodically on fractures orientated parallel to the dike plane. We interpret it as caused by fragments of chilled magma being broken and pushed along the conduit by melt flow. Laboratory experiments on basalt samples under shear strains of 104 show that the shear strength of a sample cooled through the glass transition initially increases to a maximum at 0.7 homologous temperature, but subsequently decreases until failure at 0.58 homologous temperature. We interpret the failure as due to the connection of microcracks. Episodicity in microseismicity on timescales of hours to days can arise from a cycle in which magma in 0.1–0.5 meter thick dikes first cools and becomes stronger, but then weakens along the dike margins with continued cooling against the country rock. Continued pressure of magma from below may then cause failure along dikeparallel fractures.